IMMUNOMODULATORY EFFECT OF A MIXTURE OF WATER EXTRACTS OF BETEL (PIPER BETLE L.) LEAF AND (UNCARIA GAMBIR ROXB.) GAMBIER ON PHAGOCYTIC CELLS AND MODULATION ON PHOSPHATASE ENZYME OF MICE: None - MUHAMMAD YANIS MUSDJA; AMINAH NURHADIYAH; ZILHALDIA; ANDRIA AGUSTA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study was to determine the immunomodulatory effect of a mixture of water extracts of betel (Piper betle L.) leaf and (Uncaria gambir Roxb.) gambier on phagocytic cells and modulation on phosphatase enzyme of mice. Methods: Mixture of extracts of betel leaf and gambier (ratio, 429:71) was given to seven groups of mice for 14 days with doses of 100, 200, and 400 mg/kg body weight (BW). Two kinds of immunomodulatory drug in syrup form commonly used in the treatment of infectious were used as positive controls. The peritoneal fluid of mice containing macrophage cells was isolated by performing surgery. Immunomodulatory effect was done by calculating the number of phagocytosis activity and capacity of macrophage cells of mice, and measurement of phosphatase enzyme was done using a spectrophotometer ultraviolet visible on λ=405 nm, after 1 h intraperitoneal injection Staphylococcus epidermidis on each group of mice. Immunomodulatory effects of each group of a mixture of extract were compared with negative control, normal control, and positive controls. Results: The result showed that doses administered 200 mg/kg BW of mixture extract most efficacy for both phagocytosis activity and phagocytosis capacity as well as for the results of testing for phosphatase enzyme. Based on statistical tests, it was significantly different (p≤0.05), if compared with negative controls and normal controls but not significantly different, if compared to positive controls (p≥0.05). Conclusion: Based on the results of this study, it has been obtained that a mixture of water extracts of betel (P. betle L.) leaf and (U. gambir Roxb.) gambier with a dose of 200 mg/kg BW is very potential to be used as an immunomodulatory.